Taxonomic and functional shifts in the rumen microbiome of buffalo calves under long-term strategic supplementation of phyto-feed additives - Soni, Pramod Kumar; Kala, Anju; Agarwal, Payal; Deka, Rampratim; Rahman, Habibur; Vijayalakshmy, Kennady; Chaudhary, Lal Chandra (Frontiers in Veterinary Science, 2025)
IntroductionThe present study aimed to understand the shift in the rumen microbiome of buffaloes fed diets with and without phyto-additives. The rationale was based on the hypothesis that plant-based additives can modulate the microbial population in the rumen, potentially reducing methane production and enhancing fiber degradation. Given the possibility that prolonged use of the same additives may lead to microbial adaptation and diminished efficacy, the study also investigated the effects of periodically switching additives.MethodsThree male buffalo calves were fed a control diet, while another three received additive-supplemented diets. Two additive formulations were used: FAI (a blend of garlic Allium sativum, ajwain Trachyspermum ammi, harad Terminalia chebula, and soapnut Sapindus mukorossi) and FAII (ajwain oil). The additives were alternated every 15 days to prevent microbial adaptation. After 21 days of feeding, rumen liquor samples were collected 2 hours post-feeding for metagenomic analysis. The study included both in vivo and in vitro assessments of rumen fermentation.ResultsMetagenomic analysis revealed that dominant bacterial phyla included Prevotella, Bacteroides, Succiniclasticum, Fibrobacter, Clostridium, Alistipes, Ruminococcus, and Butyrivibrio, with over 50 bacterial species consistently present across all animals. The main archaeal phylum was Euryarchaeota (>85%), along with notable presence of Candidatus_Bathyarchaeota and Thaumarchaeota. At the genus level, Methanomicrobium and Methanobrevibacter each accounted for approximately 30% of the archaeal community, followed by Methanosphaera, Methanosarcina, and Methanomassiliicoccus. While total abundances of Archaea and Bacteroidota were not significantly different among groups, specific taxa within these phyla showed marked changes.DiscussionThe inclusion of phyto-additives in the buffalo diet influenced the rumen microbiome composition by reducing methanogen populations, particularly Methanobrevibacter, and enhancing fiber-degrading microbial communities. These microbial shifts were associated with improved fiber utilization and decreased methane emissions. Rotating the additives every 15 days appeared to sustain their efficacy over time, potentially by preventing microbial adaptation. This approach may offer a sustainable strategy to optimize rumen function and reduce enteric methane emissions in ruminants.